(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Pediatric oral surgery aims to minimize trauma, reduce pain, and preserve developing structures. Piezoelectric surgery, an ultrasonic bone-cutting technique, has been proposed as an alternative to conventional rotary instruments. Objective: To synthesize existing evidence comparing piezoelectric and conventional approaches in pediatric oral surgery, focusing on clinical outcomes in primary and early third molar extractions. Summary: Evidence indicates that piezosurgery reduces intraoperative bleeding, postoperative pain, swelling, and accelerates recovery. Operative time is consistently longer compared with rotary techniques. Pediatric-specific data are limited but suggest advantages in comfort, safety near developing tooth buds, and faster functional return. Conclusion: Piezoelectric surgery offers promising clinical benefits in children but requires validation through high-quality pediatric trials before routine adoption.